Correlates of physical activity among children with visual impairments. Issue 2 (April 2019) - Brian, Ali; Pennell, Adam; Haibach-Beach, Pamela; Foley, John; Taunton, Sally; Lieberman, Lauren J.
Abstract: Background: Children with visual impairments (VI) often reveal higher levels of sedentary time and lower levels of fundamental motor skills (FMS), health-related fitness (HRF) and physical activity (PA) than peers without visual impairments. Extrapolating correlates of HRF and PA are important to develop targeted intervention strategies aimed at improving health- and movement-based outcomes. Objective: The purpose of this study was to examine associations among FMS (divided into locomotor and object control skills), HRF, and home- and sport-camp based PA measures in children with VI. Methods: Children with VI ( N =  66; 9–18 years) completed PA, HRF (including cardio-respiratory fitness, muscular strength and endurance), and FMS measures during a seven-day period. Partial and zero-order correlations, which included controlling for age, degree of VI, and BMI z -score were performed. Results: When controlling for vision, age, and BMI z -score, home-based self-report PA moderately correlated with camp-based accelerometer data ( p <  .001); home-based and camp-based PA associated with object control and locomotor subscales ( p <  .001); object control and locomotor skills were the most influential factors above and beyond vision associating with both PA measures. Cardiorespiratory fitness and grip strength were significantly associated with both object control and locomotor skills ( p <  .001). Conclusions: Future intervention strategies that target increasing PA and HRF levels for children with VI should consider focusing upon both object control and locomotor skill development.